2005
DOI: 10.1074/mcp.m500090-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Protein Expression and Oxidative Modification in R6/2 Transgenic Mice

Abstract: Huntington disease (HD) is a hereditary neurodegenerative disorder characterized by motor, psychiatric, and cognitive symptoms. The genetic defect responsible for the onset of the disease, expansion of CAG repeats in exon 1 of the gene that codes for huntingtin on chromosome 4, has been unambiguously identified. On the other hand, the mechanisms by which the mutation causes the disease are not completely understood yet. However, defects in energy metabolism of affected cells may cause oxidative damage, which h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
147
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 168 publications
(156 citation statements)
references
References 75 publications
9
147
0
Order By: Relevance
“…Decreased PDH complex detected in HD patient's caudate nucleus was further correlated with increasing duration of the illness (Butterworth et al, 1985). Moreover, PDH expression was shown to decrease with age in the striatum of R6/2 transgenic mice (Perluigi et al, 2005). Previously, we also showed that HD cybrids present increased ROS production, compared to CTR cybrids (Ferreira et al, 2010); therefore we cannot exclude modifications in PDH activity resulting from enzyme oxidation.…”
Section: Discussionmentioning
confidence: 86%
“…Decreased PDH complex detected in HD patient's caudate nucleus was further correlated with increasing duration of the illness (Butterworth et al, 1985). Moreover, PDH expression was shown to decrease with age in the striatum of R6/2 transgenic mice (Perluigi et al, 2005). Previously, we also showed that HD cybrids present increased ROS production, compared to CTR cybrids (Ferreira et al, 2010); therefore we cannot exclude modifications in PDH activity resulting from enzyme oxidation.…”
Section: Discussionmentioning
confidence: 86%
“…and GST activity-We have previously shown that the oxidative modification of specific enzymes generally decreases their activity [82,92]. Therefore, in the present study we hypothesized that since increased oxidation leads to loss of enzymatic activity, then protection from oxidative damage could restore or maintain the activity of enzymes with up-regulated expression levels.…”
Section: Superoxide Dismutase (Sod)mentioning
confidence: 77%
“…Two-dimensional electrophoresis offers an excellent tool for the screening of abundant protein changes in various disease states [21,22,82,88]. In the present study, we investigated the pattern of protein expression in the parietal cortex in the four different groups.…”
Section: Protein Expression Levelsmentioning
confidence: 98%
See 1 more Smart Citation
“…Many proteins have been demonstrated to interact with WT Htt and/or mutant Htt, and their functions support some of the mechanisms perturbed in HD, which include transcription, signaling, trafficking/endocytosis, and metabolism/mitochondrial functions (5)(6)(7)(8)(9)(10). However, Htt's precise function has proven elusive, and our poor understanding of its function remains a limiting factor to the development of successful therapeutics (11).…”
mentioning
confidence: 99%